2021
DOI: 10.1093/infdis/jiab633
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adjuvanted Zoster Vaccine and Reduced Risk of Coronavirus Disease 2019 Diagnosis and Hospitalization in Older Adults

Abstract: Background Some vaccines elicit non-specific immune responses that may protect against heterologous infections. We evaluated the association between recombinant adjuvanted zoster vaccine (RZV) and COVID-19 outcomes at Kaiser Permanente Southern California. Methods In a cohort design, adults aged ≥50 years who received ≥1 RZV dose before 3/1/2020 were matched 1:2 to unvaccinated individuals and followed until 12/31/2020. Adjus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…For HZV, the recent introduction of adjuvanted recombinant herpes zoster vaccine has dramatically improved vaccine efficacy compared to live attenuated zoster vaccines. Indeed, whereas live attenuated varicella zoster vaccine presented age-dependent vaccine efficacy, dropping from 64% in the 60-69 age group to 41% in the 70-79 age group, herpes zoster adjuvanted recombinant vaccine has demonstrated elevated and age-independent vaccine efficacy [22,36,37], corroborated by the previous reported evidence of the possible protection against severe COVID-19 symptoms [34].…”
Section: Tailored Vaccinology As a Way To Overcome Immunosenescencesupporting
confidence: 64%
See 2 more Smart Citations
“…For HZV, the recent introduction of adjuvanted recombinant herpes zoster vaccine has dramatically improved vaccine efficacy compared to live attenuated zoster vaccines. Indeed, whereas live attenuated varicella zoster vaccine presented age-dependent vaccine efficacy, dropping from 64% in the 60-69 age group to 41% in the 70-79 age group, herpes zoster adjuvanted recombinant vaccine has demonstrated elevated and age-independent vaccine efficacy [22,36,37], corroborated by the previous reported evidence of the possible protection against severe COVID-19 symptoms [34].…”
Section: Tailored Vaccinology As a Way To Overcome Immunosenescencesupporting
confidence: 64%
“…For instance, a meta-analysis showed that all-cause mortality in children was reduced by 49% after administration of measles vaccination [ 17 , 32 ], and studies have found a correlation between BCG vaccination and reduced COVID-19 mortality [ 17 , 33 ]. In addition, the EPI-ZOSTER-089 study assessed whether recombinant herpes zoster vaccination (RZV) resulted in a lower risk of COVID-19 [ 34 ]. The study involved two approaches, namely, a matched cohort and a test negative approach, in order to reduce the risk of bias; the two approaches provided consistent results.…”
Section: Trained Immunity and The Role Of Adjuvantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unrelated live attenuated vaccines and adjuvanted vaccines can provide sustained protection against heterologous infections and severe outcomes, including COVID-19, possibly through induction of trained innate immunity, which mRNA vaccines also induce. 31 , 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…To the Editor —We read with great interest the article by Bruxvoort et al reporting that recombinant adjuvanted zoster vaccine vaccination was associated with a lower risk of coronavirus disease 2019 (COVID-19) diagnosis and COVID-19 hospitalization [ 1 ]. We wish to highlight some key points.…”
mentioning
confidence: 99%